1984
DOI: 10.1159/000206384
|View full text |Cite
|
Sign up to set email alerts
|

Handmirror Cells and Central Nervous System Relapse in Childhood Acute Lymphoblastic Leukaemia

Abstract: In 53 children with acute lymphoblastic leukaemia (ALL), initial handmirror cell (HMC) count among lymphoblasts was studied in relation to the occurrence of a relapse in the central nervous system (CNS), taking into account the white blood cell count (WBC) and the immunological phenotype. The children were followed for a period limited by (1) the first CNS relapse, (2) death or (3) the closing day of this study. The median follow-up period was 30 months, range 2–106 months. HMC counts were available in bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…When we compared the di rectly observed cell motility with results of counting HMC or anti-HLA-capping, no correlation was found. HMC were counted in cytospins, according to Hogeman et al [17], who found these better reprodu cible than in blood and bone marrow smears. This is probably caused by the standardized way of prepara tion and by elimination of serum factors influencing HMC formation [18].…”
Section: Discussionmentioning
confidence: 99%
“…When we compared the di rectly observed cell motility with results of counting HMC or anti-HLA-capping, no correlation was found. HMC were counted in cytospins, according to Hogeman et al [17], who found these better reprodu cible than in blood and bone marrow smears. This is probably caused by the standardized way of prepara tion and by elimination of serum factors influencing HMC formation [18].…”
Section: Discussionmentioning
confidence: 99%